2013
DOI: 10.3390/rs6010407
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing-Derived Bathymetry of Lake Poopó

Abstract: Located within the Altiplano at 3,686 m above sea level, Lake Poopó is remarkably shallow and very sensitive to hydrologic recharge. Progressive drying has been observed in the entire Titicaca-Poopó-Desaguadero-Salar de Coipasa (TPDS) system during the last decade, causing dramatic changes to Lake Poopó's surface and its regional water supplies. Our research aims to improve understanding of Lake Poopó water storage capacity. Thus, we propose a new method based on freely available remote sensing data to reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 38 publications
0
54
0
Order By: Relevance
“…Some levels of decline (shrinkage) of lakes, such as Ihema, Mihindi and Kivumba, have been noted, while some levels of increase (expansion) have been reported on Lake Rwanyakizinga. The decline in waterbodies' extents may be triggered by a number of reasons, including, but not limited to, an increase in sedimentation, as well as retreating water levels due to high evaporation as a result of the increase in temperature, as was the case for Lake Chad, Lake Alemaya in Ethiopia, and Lake Poopó in Bolivia [31][32][33], and invasive species. However, given that previous studies on the evolution of climatic conditions in this area have indicated their benign effect to water reservoirs and that no sedimentation increases have been reported, the former two assumptions may be discarded.…”
Section: Lakes' Surface Water Extent Dynamicsmentioning
confidence: 99%
“…Some levels of decline (shrinkage) of lakes, such as Ihema, Mihindi and Kivumba, have been noted, while some levels of increase (expansion) have been reported on Lake Rwanyakizinga. The decline in waterbodies' extents may be triggered by a number of reasons, including, but not limited to, an increase in sedimentation, as well as retreating water levels due to high evaporation as a result of the increase in temperature, as was the case for Lake Chad, Lake Alemaya in Ethiopia, and Lake Poopó in Bolivia [31][32][33], and invasive species. However, given that previous studies on the evolution of climatic conditions in this area have indicated their benign effect to water reservoirs and that no sedimentation increases have been reported, the former two assumptions may be discarded.…”
Section: Lakes' Surface Water Extent Dynamicsmentioning
confidence: 99%
“…To perform this variable, we can use a combination of a lake's water height and water surface extent at different dates and then establish a relationship between these variables and water volume changes. This calculation has been used in many published studies (for an example see Gao et al 2012;Duan and Bastiaanssen 2013;Arsen et al 2014). The first step relates to using satellite imagery to compute several lakes' water mask therein corresponding to concomitant water heights.…”
Section: Satellite Imagerymentioning
confidence: 99%
“…Low-resolution bias is the inaccuracy introduced by the differences in spatial resolution between high and low-resolution data (Boschetti et al 2014). This surface bias must be estimated in order to properly translate results obtained with one resolution to another (e.g., Arsen et al 2014). For the Hydroweb database, the hypsometry of lakes is estimated with no more than 10-15 images (information given).…”
Section: Satellite Imagerymentioning
confidence: 99%
“…Morris and Gill, 1994;Crétaux and Birkett, 2006;Calmant et al, 2008;Gao et al, 2012;Wang et al, 2013), or their bathymetry (Arsen et al, 2014). Orbit repeat periods of radar altimeters such as Topex/Poseidon (T/P), GFO, Jason-1 and 2, or Envisat range from 10 to 35 days.…”
Section: N Avisse Et Al: Monitoring Small Reservoirs' Storagementioning
confidence: 99%